The Regime is Dead! Long Live the Regime! - Lallana, Emmanuel C. (Kasarinlan: Philippine Journal of Third World Studies; Vol 1 No 4 (1985), 2007)
This paper examines the critical factors and key players that have lead and contributed to the demise of the Marcos regime. The assassination of “Ninoy” Aquino and the consequent rise of his widow “Cory”, imposition of martial law, popular dissatisfaction with Marcos’ rule, massive government bailout of bankrupt crony firms and the loss of support and discontent from the national, landed and petty-bourgeoisie, were the tell-tale signs of Marcos’ besieged regime. Another crucial juncture in the series of events was the military mutiny which was popularly supported by the people. This in turn created a situation of dual power. In the wake of the Marcos’ regime, majority of Left organizations were marginalized from the political process. The absence of the Left allowed for succeeding battles to be promoted in Christian terms. Because no group articulated coherent and dynamic interpretation of the events other than the Church, the opportunity to raise the political understanding of the people was lost. The paper also provides a reflection on the so-called success of the people to bring down Marcos by understanding what was accomplished and what remains to be done. One of the challenges born by the aftermath includes moving towards formal, if not substantive, democracy. A specific stride towards this direction is for the movement that overthrew Marcos to have a cohesive ideology that goes beyond the personal commitment to Cory Aquino.
Keywords: Marcos regime, crony firms, the Left, military, formal democracy, dual power